How the Innate Immune System of the Blood Contributes to Systemic Pathology in COVID-19-Induced ARDS and Provides Potential Targets for Treatment - Nilsson, Bo; Persson, Barbro; Eriksson, Oskar; Fromell, Karin; Hultström, Michael; Frithiof, Robert; Lipcsey, Miklos; Huber-Lang, Markus; Ekdahl, Kristina N. (Frontiers in Immunology, 2022)
Most SARS-CoV-2 infected patients experience influenza-like symptoms of low or moderate severity. But, already in 2020 early during the pandemic it became obvious that many patients had a high incidence of thrombotic complications, which prompted treatment with high doses of low-molecular-weight heparin (LMWH; typically 150-300IU/kg) to prevent thrombosis. In some patients, the disease aggravated after approximately 10 days and turned into a full-blown acute respiratory distress syndrome (ARDS)-like pulmonary inflammation with endothelialitis, thrombosis and vascular angiogenesis, which often lead to intensive care treatment with ventilator support. This stage of the disease is characterized by dysregulation of cytokines and chemokines, in particular with high IL-6 levels, and also by reduced oxygen saturation, high risk of thrombosis, and signs of severe pulmonary damage with ground glass opacities. The direct link between SARS-CoV-2 and the COVID-19-associated lung injury is not clear. Indirect evidence speaks in favor of a thromboinflammatory reaction, which may be initiated by the virus itself and by infected damaged and/or apoptotic cells. We and others have demonstrated that life-threatening COVID-19 ARDS is associated with a strong activation of the intravascular innate immune system (IIIS). In support of this notion is that activation of the complement and kallikrein/kinin (KK) systems predict survival, the necessity for usage of mechanical ventilation, acute kidney injury and, in the case of MBL, also coagulation system activation with thromboembolism. The general properties of the IIIS can easily be translated into mechanisms of COVID-19 pathophysiology. The prognostic value of complement and KKsystem biomarkers demonstrate that pharmaceuticals, which are licensed or have passed the phase I trial stage are promising candidate drugs for treatment of COVID-19. Examples of such compounds include complement inhibitors AMY-101 and eculizumab (targeting C3 and C5, respectively) as well as kallikrein inhibitors ecallantide and lanadelumab and the bradykinin receptor (BKR) 2 antagonist icatibant. In this conceptual review we discuss the activation, crosstalk and the therapeutic options that are available for regulation of the IIIS.